2014
DOI: 10.1002/art.38696
|View full text |Cite
|
Sign up to set email alerts
|

The Discoidin Domain Receptor 2/Annexin A2/Matrix Metalloproteinase 13 Loop Promotes Joint Destruction in Arthritis Through Promoting Migration and Invasion of Fibroblast‐like Synoviocytes

Abstract: Objective. Discoidin domain receptor 2 (DDR-2)/ matrix metalloproteinase (MMP) signaling is an important pathway involved in cartilage destruction in rheumatoid arthritis (RA). However, the molecular mechanisms of this pathway have not been clearly identified. This study was undertaken to screen key molecules involved in this pathway and evaluate their biologic functions in synovium invasion of RA.Methods. DDR-2-interacting proteins were examined in vitro by immunoprecipitation and mass spectrometry, and annex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 43 publications
3
42
0
Order By: Relevance
“…We uncovered the Collagen II–DDR2–activator protein 1 (AP‐1)–CYR61–ETS1–MMP1 loop in RA FLS. Considering our previously findings that DDR2 activated by Collagen II promotes MMP13 through regulating Runx‐2, AP‐1, or annexin A2, this study shed new lights on the mechanism of DDR2 in RA and all our data collectively showed that DDR2 regulates MMPs production via several reciprocal and overlapped signaling pathways and blockade of DDR2 activation may be a new economical and effective strategy for RA treatment.…”
Section: Introductionsupporting
confidence: 60%
“…We uncovered the Collagen II–DDR2–activator protein 1 (AP‐1)–CYR61–ETS1–MMP1 loop in RA FLS. Considering our previously findings that DDR2 activated by Collagen II promotes MMP13 through regulating Runx‐2, AP‐1, or annexin A2, this study shed new lights on the mechanism of DDR2 in RA and all our data collectively showed that DDR2 regulates MMPs production via several reciprocal and overlapped signaling pathways and blockade of DDR2 activation may be a new economical and effective strategy for RA treatment.…”
Section: Introductionsupporting
confidence: 60%
“…synoviocytes from patients with rheumatoid arthritis are particularly able to invade and destroy joints (28)(29)(30). Careful histological observations of the architecture of fibrosis also suggest an important contribution of fibroblast invasion to IPF pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In murine collagen-induced arthritis, annexin A2 promoted migration and invasion of fibroblast synoviocytes into cartilage, leading to cartilage destruction. Conversely, down-regulation of annexin A2 expression alleviated joint damage [29]. Moreover, annexin A2 levels in synovial tissue were higher in RA patients than in OA patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, down-regulation of annexin A2 expression alleviated joint damage [29]. Moreover, annexin A2 levels in synovial tissue were higher in RA patients than in OA patients [29]. …”
Section: Discussionmentioning
confidence: 99%